Morphology and Histochemistry of the Liver of Carnivorous Fish Hemisorubim platyrhynchos - Faccioli, Claudemir Kuhn [UNESP]; Chedid, Renata Alari [UNESP]; Bombonato, Maria Terezinha Siqueira [UNESP]; Vicentini, Carlos Alberto [UNESP]; Vicentini, Irene Bastos Franceschini [UNESP] (Soc Chilena Anatomia, 2014)
The aim of this study was to characterize the normal structure of the liver of Hemisorubim platyrhynchos, a carnivorous freshwater catfish found in Neotropical region, using gross anatomy, histology and histochemistry. Anatomically, the liver presents C-shaped and only two lobes: smaller right and bigger left. The gallbladder is located in right lobe and shows elongated shaped. Histological analysis demonstrated that the hepatic parenchyma is made of two hepatocytes plates surrounded by sinusoids. The hepatocytes are polygonal-shaped cells, with spherical nucleus and a dark prominent nucleolus. The cytoplasm presents large amount of lipids and glycogen deposits PAS positives. There are no hepatic lobules or portal triads. Bile ducts are lined by columnar epithelial cells with apical mucosubstances PAS and AB positive. Furthermore, the liver presents melano-macrophages centers, distributed next to the blood vessels and bile ducts, constituted by cells accumulating pigments, whose presence may be related to the nutritional status of the fish. Moreover pancreatic tissue was observed in visceral portion of liver, formed by exocrine pancreatic tissue and islet organ, constituting an extrahepatic pancreas.
Morfología e histoquímica del hígado del pez carnívoro Hemisorubim Platyrhynchos
Keywords: Anatomy; Histology; Hepatocytes; Extrahepatic pancreas; Teleost; Anatomía; Histología; Hepatocitos; Páncreas extrahepático; Teleósteos